Improving Language Feature Understanding of Story on Video Through Developing Moodle-Based E-Learning - Antoni, Nur; Kurniawan, Asep (Universitas Negeri Semarang, 2022)
In this pandemic situation, English learning mostly has been done online. Hence it’s tutor job to be creative. Moodle based e learning hoped give solution.This study has purpose to: (1) produce an appropriate Moodle-based English e-learning product in improving language features of story understanding at Jovelin Course (2) find out how effective Moodle-based e-learning is on language features of story understanding at Jovelin Course. This research uses Research Development. Data collection instruments are interviews, questionnaires, and tests. The following is the study's findings. (1) An online Learning Management System (LMS) based on the Moodle application software version 3.1 was used to produce the e-learning offering. (2) Based on media expert validation with a score of 3.68 with